Differences in the Wavelength of Sound that Can be Received and Heard by Bats, Dolphins and Humans and Their Positive and Negative Impacts - nisa, khoirun; Maghfiro, Nur’afnimaulina; Nurlaili, Eva; Khofifah, Siti (Journal of Biomedical and Techno Nanomaterials, 2024)
Sound is a longitudinal wave. Sound has a frequency, based on the number of frequencies sound is divided into 3, infrasonic, audiosonic, and ultrasonic. Humans can hear audiosonic sounds while dolphins and bats hear ultrasonic sounds. This difference in frequency also affects the wavelength of the sound produced. The relationship between frequency and wavelength is an inverse ratio, which means that the higher the frequency, the lower the sound waves, and vice versa. Infrasonic sound for humans and ultrasonic for dolphins and bats each have positive and negative impacts. In humans, infrasonic sound has the benefit of being comfortable in hearing, but when the sound is too high it can also reduce brain balance which results in ear damage. While the ultrasonic sound in the hearing of dolphins and bats has the advantage of helping them find food, even in dolphins can help communicate. But in bats this ultrasonic sound cannot be used to communicate like dolphins